Relative age effects and place of early development constrain male youth Italian swimmers` developmental experiences - Morganti, G.; Kelly, A. L.; Vitarelli, M.; Strassoldo di Villanova, F.; Ruscello, B.; Campoli, F.; Padua, E. (Sports, 2024)
Italian swimming emphasizes the early specialization of selected children from approximately 6 to 7 years old. Such an approach often leads to selection biases (i.e., birth advantages), which may undermine swimmers` development and progression through the talent pathway. Accordingly, this study aimed to: (a) explore the presence of birth advantages at the annual Italian national age-group competition by observing the birth quarter (BQ) and place of early development (PED) distribution of 514 U15 swimmers; and (b) investigate how birth advantages affect swimmers` ability to maintain their national status by comparing the BQ and PED distributions of 555 U17 national-level swimmers to the expected values (i.e., U15 distribution). Chi-square statistics for the U15 revealed an overrepresentation of BQ1s and swimmers developing in north and central Italy (p-values < 0.0001). In contrast, the U17`s BQ (p < 0.001) and PED (p = 0.01) distributions appeared skewed compared to the U15, favoring swimmers born in BQ3 and BQ4, and swimmers developing in north Italy (odds ratios: 1.69, 1.76, 1.39 respectively). The findings highlighted that cultural-contextual features of the environment shape Italian youth swimmers` development and their progression through the current talent pathway.